2019
DOI: 10.2147/idr.s183151
|View full text |Cite
|
Sign up to set email alerts
|

<p>Genotypic characterization of <em>Pseudomonas aeruginosa</em> isolates from Turkish children with cystic fibrosis</p>

Abstract: Objective: To identify epidemic and other transmissible Pseudomonas aeruginosa strains, genotypic analyses are required. The aim of this study was to assess the distribution of P. aeruginosa strains within the Turkish pediatric cystic fibrosis (CF) clinic population. Methods: Eighteen patients attending the pediatric CF clinic of Cerrahpasa Medical Faculty were investigated in the study. Throat swab and/or sputum samples were take… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 33 publications
1
1
0
Order By: Relevance
“…There were only two identical pulsotypes (identity more than 85%) in the tested isolates. Similar to one study in Turkey, 40 we found that the isolates in shared pulsotypes (pulsotypes C and J) did not have similar antimicrobial resistance patterns. We followed the hospital records of the patients in pulsotypes C and J and found that both patients in pulsotype J (patients 9, a 49 years old man, and patient 10, a 25 years old woman) had been hospitalized in same ward (ICU) of one hospital (hospital A) on the same dates.…”
Section: Discussionsupporting
confidence: 83%
“…There were only two identical pulsotypes (identity more than 85%) in the tested isolates. Similar to one study in Turkey, 40 we found that the isolates in shared pulsotypes (pulsotypes C and J) did not have similar antimicrobial resistance patterns. We followed the hospital records of the patients in pulsotypes C and J and found that both patients in pulsotype J (patients 9, a 49 years old man, and patient 10, a 25 years old woman) had been hospitalized in same ward (ICU) of one hospital (hospital A) on the same dates.…”
Section: Discussionsupporting
confidence: 83%
“…that were found in the investigated samples are mainly bacteria living in the natural environment and are an opportunistic pathogen. It often causes chronic lung infections associated with respiratory failure, clinic deterioration or burn patients 48,49. However, it should be pointed out that they are a source of endotoxins too.…”
Section: Discussionmentioning
confidence: 99%